Hydrogen concentration and hydrides in Zircaloy-4 during cyclic thermomechanical loading. (December 2021) - Liu, Yang; Chamaa, Said El; Wenman, Mark R.; Davies, Catrin M.; Dunne, Fionn P.E.
Abstract: Hydride formation in Zircaloy-4 under cyclic thermomechanical loading has been investigated using characterized notched beam samples in four-point beam testing, and microstructurally-representative crystal plasticity modelling of the beam tests which incorporates an atomistically-informed equilibrium-state model for hydrogen concentration. The model provided the locations within the microstructure of high hydrogen content, above that required for saturation, hence predicting the anticipated locations of hydride observations in the experiments. The strain rate sensitivity of this alloy over the temperature range considered led to considerable intragranular slip and corresponding stress redistribution, and cyclic strain ratcheting leading to high hydrostatic stresses and in turn hydrogen concentrations, which explains the locations of experimentally observed hydride formation. The interstitial hydrogen interaction energy as well as the intragranular geometrically necessary dislocation density were shown to be important in controlling the spatial distributions of observed hydrides. Graphical abstract: Image, graphical abstract